2013
DOI: 10.1260/1708-5284.10.4.359
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of physical and mechanical properties of rock for drilling condition classification

Abstract: This work deals with the investigation of physical and mechanical properties of selected rocks for condition of drilling categorization. Rock samples collected from five drilling locations were tested in the laboratory for uniaxial compressive strength, tensile strength, and Drilling Rate Index (DRI) using 1,100 kN compression machine, point load tester and miniature drill. Similarly, hardness, brittleness, Rock Abrasivity Index (RAI), penetration rate and bit wear rate were determined. The results showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Therefore, performing a simulation based on the physical, mechanic, and plasticity properties during the disposal slope design process is necessary to obtain optimum safety value by referring to the weakest material and serves as a guide in determining the proper disposal geometry in mine design. (Renema et al, 2015) that vary from one location to another (Adebayo and Adetula, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, performing a simulation based on the physical, mechanic, and plasticity properties during the disposal slope design process is necessary to obtain optimum safety value by referring to the weakest material and serves as a guide in determining the proper disposal geometry in mine design. (Renema et al, 2015) that vary from one location to another (Adebayo and Adetula, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The design aspects and possibilities for sharing failures that must be studied are parts of the investigation. In a study by Adebayo and Adetula (2013) [11], it was established that uniaxial compressive strength, texture and grain size, drill rate index and equivalent quartz content (EQC) significantly affect rock drilling conditions. Appropriate laboratory tests, therefore, need to be carried out before the final design stage to assess the rock properties.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al (2002) pointed out that the relationship between effective confining pressure and Young's modulus, compressive strength, is exponential through the core measurement but did not construct continuous changing model of mechanics properties in the process of water flooding; You (2003) believed that law of Young's modulus changing with the confining pressure reflects the rock internal damage state by measuring the cores with different lithology, and he thought that average Young's modulus value will be accurate relatively when considering the heterogeneity of the rock at the same time; Zeng et al (2012) put forward the storage and seepage unit which consists of sedimentation, diagenesis, and tectogenesis by using the method of clustering analysis to evaluate reservoir anisotropy of low-permeability sandstones. Yu and Tian (2013) calculated the anisotropic coefficient when rock mass mechanics parameters changed with confining pressure and predicted the relationship between the elastic modulus and depth; Adebayo and Adetula (2013) determined the hardness, brittleness, Rock Abrasivity Index (RAI), penetration rate, and bit wear rate to study the condition of drilling categorization. Tang (2014) analyzed wave velocities and modulus of the anisotropic rock under the condition of quasi static and dynamic state, he believed that anisotropic characteristics was related to porosity, compaction history, and particle composition; Nishimura (2014) used a new type of tri-axial test instrument to quantify the small strain of rock material value in high precision, which could help to get more accurate determination of anisotropic Young's modulus; Kongkitkul et al (2014) determined Young's modulus of two kinds of new asphalt materials, and concluded that the vertical of Young's modulus is greater than that of the horizontal.…”
Section: Introductionmentioning
confidence: 99%
“…(2012) put forward the storage and seepage unit which consists of sedimentation, diagenesis, and tectogenesis by using the method of clustering analysis to evaluate reservoir anisotropy of low-permeability sandstones. Yu and Tian (2013) calculated the anisotropic coefficient when rock mass mechanics parameters changed with confining pressure and predicted the relationship between the elastic modulus and depth; Adebayo and Adetula (2013) determined the hardness, brittleness, Rock Abrasivity Index (RAI), penetration rate, and bit wear rate to study the condition of drilling categorization. Tang (2014) analyzed wave velocities and modulus of the anisotropic rock under the condition of quasi static and dynamic state, he believed that anisotropic characteristics was related to porosity, compaction history, and particle composition; Nishimura (2014) used a new type of tri-axial test instrument to quantify the small strain of rock material value in high precision, which could help to get more accurate determination of anisotropic Young's modulus; Kongkitkul et al.…”
Section: Introductionmentioning
confidence: 99%